PENGELOLAN EVALUASI WISATA LUAR NEGERI - Priska Reza Lestari; Putri Anti; Muhammad Zamzam (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The management and evaluation of international tourism are essential aspects of the tourism industry that determine the success of travel activities. This study aims to analyze the management and evaluation processes of international tourism in improving service quality and tourist satisfaction. The research employs a library research method with a descriptive qualitative approach by collecting data from various recent scientific journals and literature sources. The results indicate that international tourism management consists of planning, organizing, implementing, and controlling stages that must be carried out systematically and in an integrated manner. Furthermore, evaluation is conducted through tourist satisfaction analysis, tour guide performance assessment, and the utilization of digital technology as a feedback collection tool. The use of technology in evaluation enables tourism organizers to obtain more accurate and objective data. Therefore, effective management and evaluation can enhance service quality, provide optimal travel experiences, and strengthen the competitiveness of the tourism industry at a global level.